2018
DOI: 10.1016/j.agee.2017.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable intensification through rotations with grain legumes in Sub-Saharan Africa: A review

Abstract: HighlightsWe retrieved 44 publications and 199 observations comparing continuous cereal with grain legume-cereal rotation in SSA.Cereal after legume yielded on average 0.49 t grain ha−1 or 41% more than continuous cereal.Sustained residual benefits of legumes with large N applications indicate the importance of non-N effects.Relevant non-N effects include improved P availability, changes in SOM, and in pest, disease and striga pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
196
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(205 citation statements)
references
References 136 publications
(214 reference statements)
5
196
2
2
Order By: Relevance
“…Inclusion of leguminous crops in cropping systems can reduce the mineral fertilizer N requirement for the subsequent crop (Jensen et al, 2012). A meta-analysis for SSA revealed that this residual effect of legumes can result in 450-700 kg/ha extra maize yield (Franke, Van Den Brand, Vanlauwe, & Giller, 2017). This potentially lowers the input of mineral fertilizer by 0-51 kg N/ha resulting in 0.03-12.18 Mton CO 2 eqv.…”
Section: Methodological Considerations and Uncertaintiesmentioning
confidence: 99%
“…Inclusion of leguminous crops in cropping systems can reduce the mineral fertilizer N requirement for the subsequent crop (Jensen et al, 2012). A meta-analysis for SSA revealed that this residual effect of legumes can result in 450-700 kg/ha extra maize yield (Franke, Van Den Brand, Vanlauwe, & Giller, 2017). This potentially lowers the input of mineral fertilizer by 0-51 kg N/ha resulting in 0.03-12.18 Mton CO 2 eqv.…”
Section: Methodological Considerations and Uncertaintiesmentioning
confidence: 99%
“…Increased productivity of maize after a grain legume relative to maize after maize has been widely reported in the Guinea savanna of West Africa (Sauerborn et al, 2000;Sanginga et al, 2002;Franke et al, 2018). The N contributed to the soil by grain legumes and non-N benefits of rotating grain legumes with maize (pests and diseases suppression, improved soil properties, soil microbial biomass and activity) have been reported to account for the increased productivity of maize after grain legumes (Stevenson and van Kessel, 1996;Giller, 2001;Yusuf et al, 2009b).…”
Section: Cropping System Diversification With Grain Legumesmentioning
confidence: 97%
“…This suggests that the increased maize grain yield after soybean in the HF field in the NGS was largely due to non-N benefits (e.g. increased soil microbial biomass and functioning, improved soil structure, improved N mineralisation) (Giller, 2001, Sanginga et al, 2002Yusuf et al, 2009b;Franke et al, 2018). Residual effects of fixed N2 on maize performance are likely to be more important in LF fields than in HF fields, but the results from the current trial do not provide clear evidence for this.…”
Section: N2-fixation and Net N Contribution To The Soil For A Subsequmentioning
confidence: 99%
See 2 more Smart Citations